Soil cover management for coffee establishment and production. I. Influence on soil fertility - Pavan, Marcos A.; Caramori, Paulo H.; Filho, Armando Androcioli; Scholz, Marcos F. (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was conducted during seven years with coffee trees to determine the influence of some management practices on the fertility levels of a Red Yellow Latosol. Six soil managements were evaluated: 1. cleaning the tree rows/disking between tree rows; 2. cleaning the tree rows/retaining a permanent soil cover between the tree rows with Elionurus candidus; 3. cleaning the tree rows/retaining a permanent soil cover between the tree rows with Stylosanthes guianensis; 4. Grass mulch in the tree rows/disking between the tree rows; 5. grass mulch covering all the soil surface; and 6. black polythene mulch in the tree rows/disking between the tree rows. Grass residue mulch was found to be the most effective in improving soil fertility. The beneficial effects of protecting the soil surface with grass straw were associated with the amounts of plant nutrient released from the decomposing materials, increased soil organic carbon and pH, decreased exchangeable Al and enhanced nutrient ions uptake by coffee roots due to less moisture stress. Thus, the results suggest that additions of organic materials on the surface of very acid soils result in a favorable environment for root development. The potential of this soil management for small farm in the coast area of Paraná State may, therefore, be significant.